(untitled)
In this paper, we study the asymptotic behavior of solutions to a quasilinear fully parabolic chemotaxis system with indirect signal production and logistic source under homogeneous Neumann boundary conditions in a smooth bounded domain Ω⊂R^n (n ≥1), where b ≥0, γ ≥1, a_i ≥1, µ, b_i >0 (i =1,2), D, S∈ C^2([0,∞)) fulfilling D(s) ≥ a_0(s+1)^−α, 0 ≤ S(s) ≤ b_0(s+1)^β for all s ≥ 0, where a_0,b_0 > 0 and α,β ∈ R are constants. The purpose of this paper is to prove that if b ≥ 0 and µ > 0 sufficiently large, the globally bounded solution (u,v,w) with nonnegative initial data (u_0,v_0,w_0) satisfies \| u(·,t)− (bµ)^1γ \|_L^∞(Ω)+\| v(·,t)−b_1b_2a_1a_2 (bµ)^1γ \| _L^∞(Ω) +\| w(·,t)−b_2a_2(bµ)^1γ \| _L^∞(Ω) →0 as t→∞. , number=2, journal=Journal of Partial Differential Equations, year=2021, month=May, pages=129–143